KARAKTERISTIK SENSORIS PUREE PISANG TONGKA LANGIT PENDEK (Musa troglodytarum) - Tuhumury, H. C.D.; Moniharapon, E.; Souripet, A. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2018)
‘Tongka langit’ plaintain (Musa troglodytarum) is one of indigenousplantains in Maluku which contain β-carotene and certain phenoliccompounds. This research was aimed to determine the effect of cookingmethod and cooking time on the sensory characteristics of short ‘tongkalangit’ plaintain. A 5-scale hedonic and descriptive sensory evaluation wasperformed to determine panelist’ on colour, taste, texture, aroma and overalllikeness. Results showed that plaintain grilled for 5 minutes resulted inpuree with the best sensory characteristics and was preferred by panelistson colour (3.67), taste (3.70), texture (4.0), aroma (3.73) and overall (3.90).Keywords : tongka langit plantain, puree, sensory.